Knowledge about preventive dentistry versus self-reported competence in providing preventive oral healthcare - a study among Nepalese dentists - Madhu Wagle; Ganesh Acharya; Purusotam Basnet; Tordis A. Trovik (BMC, 2017)
Abstract Background Dentists' and dental healthcare providers' professional knowledge and attitude towards the prevention of oral diseases may have an impact on the oral health of the general population. The aim of this study was to describe Nepalese dentists' competency in giving preventive education and treatment to their patients, and to assess their level of knowledge about preventive dental health. Methods This was a cross-sectional study of 195 dentists (71 males and 124 females). Knowledge of preventive oral healthcare and self-reported aspects of preventive oral healthcare were assessed using a close-ended multiple-choice questionnaire. Statistical evaluation was done using chi-squared test, independent sample t-test and factor analysis as appropriate. Results More than 90% of dentists self-reported to be competent in providing preventive treatment and oral hygiene education to their patients. Female dentists reported being more competent in giving oral hygiene education than their male counterparts (p = 0.045). Dentists scored a mean of 24.06 ± 3.8 [range (15-33)] out of 56 on knowledge based on self-reported awareness of seven different aspects of preventive dentistry. More than 70% of the dentists had relatively good knowledge regarding the use of fluoride, whereas the preventive knowledge in other aspects of dental health such as frequency of sugar consumption, xylitol use, dental visits, sealant, gingival health, dental and general health was found to be limited. Conclusions The majority of participating dentists reported a high level of general competency in providing preventive treatment and oral health education to their patients, whereas their knowledge was found to be limited in some aspects of preventive dentistry.